The use of flash glucose monitoring significantly improves glycemic control in type 2 diabetes managed with basal bolus insulin therapy compared to self-monitoring of blood glucose: A prospective observational cohort study. (January 2022) - Bosi, E.; Gregori, G.; Cruciani, C.; Irace, C.; Pozzilli, P.; Buzzetti, R.
Abstract: Aim: This prospective, observational cohort study aimed to measure HbA1c change over 3–6 months in type 2 diabetes managed with basal-bolus insulin and FreeStyle Libre® Flash Glucose Monitoring System (FSL) use compared to self-monitored blood glucose (SMBG). Methods: Sixteen Italian hospitals enrolled patients with type 2 diabetes (n = 322, [109 FSL, 213 SMBG users]) using basal-bolus insulin therapy for ≥ 1 year, HbA1c 8.0–12.0% (64–108 mmol/mol), new to FSL use (<3 months) or continuing with SMBG (controls). Eligible FSL and SMBG users were matched (1:2 ratio) for baseline HbA1c (within ± 0.5%, recorded ≤ 3 months previously), study site and baseline data collection date. Results: Overall, baseline HbA1c was 8.9 ± 0.8% (74 ± 9 mmol/mol), age 67.2 ± 10.0 years, BMI 30.5 ± 6.5 kg/m 2 and insulin use duration 8.6 ± 6.6 years (mean ± SD), 56.2% were males. After 3–6 months, 234 complete cases (83 FSL, 151 SMBG users) demonstrated significantly reduced HbA1c for FSL use compared to SMBG (0.3% ± 0.12 [3 mmol/mol ± 1.3, (mean ± SE)], p = 0.0112). The difference remained statistically significant after adjusting for confounders. Conclusions: HbA1c significantly improved in basal-bolus treated type 2 diabetes after flash glucose monitoring use for 3–6 months compared to SMBG.